Value of the Ultrasound Attenuation Index for Noninvasive Quantitative Estimation of Hepatic Steatosis. (1st February 2013) - Kwon, Heon-Ju; Kim, Kyoung Won; Lee, So Jung; Kim, So Yeon; Lee, Jong Seok; Kim, Hyoung Jung; Song, Gi-Won; Kim, Sun A; Yu, Eun Sil; Lee, Jeongjin; Hwang, Shin; Lee, Sung Gyu
Abstract : Objectives: To assess the value of the ultrasound (US) attenuation index for noninvasive estimation of hepatic steatosis and determine its optimal cutoff value for severe steatosis in potential living liver donors. Methods: Two hundred forty potential donors underwent US‐guided biopsy. The target site was scanned at 4 and 8 MHz. On the sonogram, the observer drew 3 × 3‐mm square regions of interest in superficial (3‐cm) and deep (5‐cm) areas. The attenuation index was defined as the difference between superficial and deep echogenicity/superficial echogenicity × 100. On biopsy specimens, replacement of hepatic parenchyma was evaluated on a percentage scale. Severe steatosis was defined as macrovesicular fatty change of 30% or greater. Spearman rank correlation (ρ) was used to determine correlation coefficients between the attenuation index and steatosis degree; receiver operating characteristic analysis was performed to determine the optimal attenuation index cutoff value for severe steatosis. Results: The median steatosis degree was 3% (interquartile range [IQR], 0%–10%). Severe steatosis was found in 10 donors. The attenuation index ranged from –27.4 to 36.6 (median, 4.0; IQR, –1.6–10.4) at 4 MHz and –18.0 to 78.1 (median, 14.5; IQR, 7.2–21.9) at 8 MHz. There was a minimal positive correlation between steatosis and the attenuation index at 4 MHz (total steatosis: ρ = 0.339; P < .001; macrovesicular steatosis: ρ = 0.360; P < .001). However, there was a significant moderate correlation between steatosis and the attenuation index at 8 MHz (total steatosis: ρ = 0.669; P < .001; macrovesicular steatosis: ρ = 0.645; P < .001). The optimal attenuation index cutoff value for severe steatosis at 8 MHz was 31.0. Conclusions: The US attenuation index at 8 MHz is a useful indicator for noninvasive quantitative estimation of hepatic steatosis and diagnosis of severe steatosis in potential living liver donors.